Multi-Criteria Economic Analysis of a Pumped Thermal Electricity Storage (PTES) With Thermal Integration - Frate, Guido Francesco; Ferrari, Lorenzo; Desideri, Umberto (Frontiers in Energy Research, 2020)
The interest towards large scale electric energy storage technologies is increasing with the large deployment of new renewable capacity. In case of several-hours storage duration, there is no consensus on which technology is the most suited. Several technologies have been recently proposed, among which Pumped Thermal electricity Storage (PTES), which is a technology based on the idea of storing electrical energy as heat. PTES is usually less efficient than electrochemical batteries, but it is characterized by a lower cost per kWh, which could make it a suitable alternative for applications with long storage duration. In this study, a recently proposed PTES system based on the use of heat pumps and organic Rankine cycles is investigated from a thermo-economic point of view. The system is powered by both electric and low-grade thermal energy thus taking advantage of waste heat to increase the electric performance. As the system design both affects efficiency and cost, a tradeoff must be found. In this study this task was performed by means of a multi-objective optimization approach. The relation between electrical roundtrip efficiency and system cost is analyzed and the impact of several design specifications such as boundary conditions, nominal power rating and storage duration is discussed. Finally, the results are generalized by defining some cost scaling correlations. Large size configurations (5 MW of charging power for 8 h storage) may achieve equipment purchasing costs as low as 140 €/kWh and 2300 €/kW with an electrical roundtrip efficiency of 0.6. These results show that the investigated technology may be suitable in the context of large scale and long duration energy storage.